Study of Various Epoxy-Based Surface Coating Techniques for Anticorrosion Properties - T Ramakrishnan; K Raja Karthikeyan; V Tamilselvan; S Sivakumar; Durgaprasad Gangodkar; H R Radha; Anoop Narain Singh; Yosef Asrat Waji (Advances in Materials Science and Engineering)
Polyepoxides are a kind of chemical polymerization that is widely employed in several industrial purposes. Due to their macromolecular structure, polyepoxides offer superior superficial treatment and antierosion activity compared to basic organic corrosion inhibitors. During metal-inhibitor interactions, the polyepoxides outlying glacial efficient clusters operate as adsorption centers. Numerous polyepoxides have been employed as anticorrosive coating materials in both pure and cured forms, most notably for ferrite in acidic and NaOH solutions. The majority of polyepoxides operate as inhibitors of interface and mixed-type corrosion. Numerous computer models have been done to illustrate the anticorrosive properties of polyepoxides on metallic shells and their adsorption behavior. However, because the majority of polyepoxides have low solubility, they are best used as anticorrosive coating materials. Numerous polyepoxides-based coatings have been created and effectively applied on ferrite and aluminum in salt-water solution according to a review of the literature. Natural and synthetic additives can be used to further enhance the anticorrosive properties of polyepoxides coatings. This review article compiles published findings on the anticorrosive properties of pure and cured polyepoxides for a variety of metals and alloys in a variety of electrolytes.